New records of click-beetles (Coleoptera, Elateridae) from the Kemerovo Area (Western Siberia); Baltic Journal of Coleopterology; Vol. 16, № 1 - Prosvirov A. S. Aleksandr Sergeevich (2016, 2016)
Title screen